1990
DOI: 10.2307/1940245
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Scale to Predator‐Prey Spatial Correlations: An Example of Atlantic Fishes

Abstract: The signs and strengths of spatial correlations between densities of predators and their prey were scale dependent both in simulations and when calculated from acoustic transects across nearshore distributions of Atlantic cod (Gadus morhua), and its prey, capelin (Mallotus villosus). Spectral analyses of 1985 and 1986 transects indicated that spatial correlation (coherence) varied relative to: (1) the occupation of thermal refuge areas by capelin (sea temperatures <—0.5° or >8.5°C), (2) the aggregation dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(187 citation statements)
references
References 18 publications
6
180
1
Order By: Relevance
“…Our presence/absence approximation to these important plankton groups leads to reduced quantitative resolution and less variability explained when evaluating how these prey groups influence the fish distribution. Second, important factors may have been sampled, but not on an appropriate scale (see Rose & Leggett 1990). There are several indications in our data of a patchy distribution of prey and correspondingly high station-to-station variability in feeding intensity and prey items in the guts.…”
Section: Spatial Distributionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our presence/absence approximation to these important plankton groups leads to reduced quantitative resolution and less variability explained when evaluating how these prey groups influence the fish distribution. Second, important factors may have been sampled, but not on an appropriate scale (see Rose & Leggett 1990). There are several indications in our data of a patchy distribution of prey and correspondingly high station-to-station variability in feeding intensity and prey items in the guts.…”
Section: Spatial Distributionmentioning
confidence: 93%
“…An interesting question is whether the fish switch diets due to the presence of other species as observed for pollock in co-presence with capelin (Rose & Leggett 1990). In our data material there were five stations with co-occurrence of mackerel and herring in the catches during each of the years, so the material can only give indications about possible diet switch.…”
Section: Diet Overlapmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Shriner et al (2006) showed that the scale of observation profoundly influenced the spatial distribution of species richness hotspots and thus conservation planning priorities. The topic of scale has also received some attention in freshwater (Essington & Kitchell 1999, Fagan et al 2005, Kennard et al 2007, Wilson & Xenopoulos 2008 and marine fish studies (Rose & Leggett 1990, White & Warner 2007. In contrast, estuarine finfish studies rarely deal explicitly with issues of scale.…”
Section: Introductionmentioning
confidence: 99%
“…Most experimental studies, however, are performed at small (Englund & Cooper, 2003) and often rather arbitrary (Wheatley & Johnson, 2009) scales, and thus, if not scaled up properly might not provide the best insight into the problems that they were intended to address. Studies in other systems have shown that predator–prey interactions and abundance patterns vary with observational scale (e.g., bivalves: Seitz & Lipcius, 2001; fishes: Rose & Leggett, 1990; seabirds and fish: Fauchald et al., 2000). Spatially explicit models have also demonstrated that the population dynamics of a predator–prey metacommunity can be scale dependent (e.g., De Roos, Mccauley, & Wilson, 1991).…”
Section: Discussionmentioning
confidence: 99%